Environmental qualitative assessment of rivers sediments - A.R. Karbassi; M. Pazoki (Global Journal of Environmental Science and Management)
In this study, the concentrations of heavy metals (Ca, Zn, Cu, Fe, Mn, Ni) in thesediment of Shavoor River in Khuzestan Province in Iran has been investigated. After the library studies and field studies, six samples of water and sediment were taken from the river in order to evaluate heavy metal pollution in sediments. To determine the geochemical phases of metals in sediment samples the 5-step method was used for chemical separation. For quantitative assessment of the severity of contamination in the sediments, the geochemical indicators such as enriched factor (EF) and the accumulation index (Igeo) were used. Also, the statistical analyses including methods such as correlation analysis cluster analysis the (CA), were conducted.The results of the experiments showed that the organic matter deposited varies with the average of 2.49 and ranges between 1.95% and 3.43%. Samples showed concentrations of metals such as calcium, iron, manganese, copper and nickel at all the sampling points were below the global average, whereas the concentration of copper was slightly higher than the global scale. Enriched factor (EF) was calculated for the elements revealed that heavy metals are classified as non-infected. The Geo-accumulation Index showed that the studied elements were uninfected peers. Based on the results of multivariate statistical analysis it was concluded that metals such as manganese, copper, iron, nickel and zinc are mainly natural and calcium metal is likely to have an organic origin.